Use of tabletop exercises for healthcare education: a scoping review protocol - Richard Fleet; Sylvie Cossette; Marc-André Maheu-Cadotte; Amélie Frégeau; Alexis Cournoyer; Massimiliano Iseppon; Nathalie Soucy; Julie St-Cyr Bourque; Véronique Castonguay (BMJ Open)
Introduction There is a growing interest in developing interprofessional education (IPE) in the community of healthcare educators. Tabletop exercises (TTX) have been proposed as a mean to cultivate collaborative practice. A TTX simulates an emergent situation in an informal environment. Healthcare professionals need to take charge of this situation as a team through a discussion-based approach. As TTX are gaining in popularity, performing a review about their uses could guide educators and researchers. The aim of this scoping review is to map the uses of TTX in healthcare.Methods and analysis A search of the literature will be conducted using medical subject heading terms and keywords in PubMed, Medline, EBM Reviews (Evidence-Based Medicine Reviews), CINAHL (Cumulative Index of Nursing and Allied Health Literature), Embase and ERIC (Education Resources Information Center), along with a search of the grey literature. The search will be performed after the publication of this protocol (estimated to be January 1st 2020) and will be repeated 1 month prior to the submission for publication of the final review (estimated to be June 1st 2020). Studies reporting on TTX in healthcare and published in English or French will be included. Two reviewers will screen the articles and extract the data. The quality of the included articles will be assessed by two reviewers. To better map their uses, the varying TTX activities will be classified as performed in the context of disaster health or not, for IPE or not and using a board game or not. Moreover, following the same mapping objective, outcomes of TTX will be reported according to the Kirkpatrick model of outcomes of educational programs.Ethics and dissemination No institutional review board approval is required for this review. Results will be submitted for publication in a peer-reviewed journal. The findings of this review will inform future efforts to TTX into the training of healthcare professionals.